Efficiency of essential oils and nano-malate in reduction of ethylene production and extension of vase life of cut Eustoma grandiflorum Mariachii. cv. Blue flowers (Bangladesh Journal of Botany, 2018)
The effect of essential oils and nano-malate in extending the vase-life of Eustoma grandiflorum Mariachii. cv. Blue flower was investigated. The treatment with 3 mM nano-malate increased flower longevity as compared to control. Nano-malate treatment increased chlorophyll, proline and carbohydrate content and membrane stability, while descreasing ACO (ACC-oxidase activity) and MDA (malondialdehyde) content and delay of senescence and peroxidation of lipids. Thyme oil was slightly effective significantly. The application of nano-malate as preservative solutions for E. grandiflorum flowers maintained the vase life of flowers for a longer period.